The Value of Large Sections in Surgical Pathology - Maria P. Foschini; Chiara Baldovini; Yuko Ishikawa; Vincenzo Eusebi (International Journal of Breast Cancer)
Large format sections (LS) first have been introduced in breast pathology more than a century ago. Since then, they constituted for longtime a research tool to better understand breast microanatomy and the relationship between radiological images and pathological features. Similarly LS have been used to study neoplastic, inflammatory, and degenerative diseases affecting various organs, as brain, lung, gastrointentinal tract, bone, urinary tract, prostate, and placenta. Currently LS are mostly applied to diagnostic routine to better stage tumours such as prostate and breast carcinomas or to correlate radiologic imaging to gross specimens. The purpose of the present paper is to review the historical background and the basis of the applications of LS in surgical pathology, with special emphasis on breast tumours.